2021
DOI: 10.1016/j.envpol.2021.118003
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in a stream running through an underprivileged, underserved, urban settlement in São Paulo, Brazil: A 7-month follow-up

Abstract: COVID-19 pandemic has led to concerns on the circulation of SARS-CoV-2 in the environment, its infectivity from the environment and, the relevance of transmission via environmental compartments. During 31 weeks, water samples were collected from a heavily contaminated stream going through an urban, underprivileged community without sewage collection. Our results showed a statistically significant correlation between cases of COVID-19 and SARS in the community, and SARS-CoV-2 concentrations in the water. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…A few studies have evaluated the infectivity in cell cultures of SARS-CoV-2 isolated from water and sewage samples (Rimoldi et al 2020;Razzolini et al 2021;Westhaus et al 2021), and as reported in the present study, the presence of infectious SARS-CoV-2 was also not evidenced. Factors like the propagation process, susceptibility of cells and incubation time may affect the sensitivity of viral culture.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A few studies have evaluated the infectivity in cell cultures of SARS-CoV-2 isolated from water and sewage samples (Rimoldi et al 2020;Razzolini et al 2021;Westhaus et al 2021), and as reported in the present study, the presence of infectious SARS-CoV-2 was also not evidenced. Factors like the propagation process, susceptibility of cells and incubation time may affect the sensitivity of viral culture.…”
Section: Discussionsupporting
confidence: 53%
“…Mota et al (2021) and Prado et al (2021) in decentralized monitoring of SARS-CoV-2 RNA in sewages from Belo Horizonte and Rio de Janeiro, two other large Brazilian cities, showed that wastewater monitoring data is more sensitive for identifying hotspots in vulnerable areas than clinical/epidemiological data, allowing early intervention actions by public health authorities. Razzolini et al (2021) followed the evolution of SARS-CoV-2 RNA concentration for 7 months in a contaminated stream that receives raw sewage from an urban underprivileged settlement in the city of São Paulo and observed a statistically significant correlation between SARS-CoV-2 concentration in water and COVID-19 cases in the community. The authors concluded that virus concentration in the environment reflects the epidemiological status of the community.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the smaller WWTPs (CIC-Xisto, Padilha Sul, and Santa Quitéria), presented its highest correlation values with lag 1 (seven days after sampling), whereas the largest WTTPs (Atuba and Belém) showed higher correlation, respectively, with lag -1 (seven days before sampling) or lag 2 (14 days after sampling). A systematic review of correlation measurements of viral titers in sewage and the number of COVID-19 cases reported values ranging -0.38 to 0.99 (Li et al 2023b ), with studies in Brazil showing positive correlations between 0.41–0.63 (Bueno et al 2022 ), and regression coefficients ranging from 0.22–0.71 (Barbosa et al 2022 ; Razzolini et al 2021 ). In comparison to the values reported for Brazil, the ones found for Curitiba in the present study are among the highest found for the country, which can be related to the high sewer coverage in the city.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, they have been adopted successfully in several countries on all continents with human settlements (Street et al 2020 ; Ahmed et al 2020 ; Gonzalez et al 2020 ; Arora et al 2020 ; Agrawal et al 2021b , a ; Weidhaas et al 2021 ; Bar-Or et al 2021 ; Hasan et al 2021 ; Saththasivam et al 2021 ; Carrillo-Reyes et al 2021 ; Wu et al 2021 ; Yaniv et al 2021 ; Giraud-Billoud et al 2021 ). In Brazil, the monitoring and quantification of viral ribonucleic acid (RNA) as a tool for epidemiological monitoring was readily implemented in some cities, with published reports from Niteroi (Rio de Janeiro State) (Prado et al 2020 , 2021 ), São Paulo and adjacent cities (São Paulo State) (Claro et al 2021 ; Razzolini et al 2021 ; Barbosa et al 2022 ; Bueno et al 2022 ; Martins et al 2022 ), Belo Horizonte (Minas Gerais State) (Chernicharo et al 2020 ; Mota et al 2021 ) and rural settings in southeastern Minas Gerais (Fongaro et al 2021 ), Goiânia (Goiás State), the Federal District, and Foz do Iguaçu (Paraná State) (Bueno et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from several countries have reported the presence of the novel coronavirus in wastewater, including the Netherlands (Medema et al 2020 ), USA (Duvallet et al 2022 ; Sherchan et al 2020 ; Toledo et al 2022 ), UK (Wade et al 2022 ), South Africa (Tlhagale et al 2022 ), Japan (Tanimoto et al 2022 ; Zhu et al 2022 ), France (Foladori et al 2020 ; Wurtzer et al 2020 ), Italy (Rimoldi et al 2020a , 2020b ; Forthomme 2020 ), Spain (Chavarria-Miró et al 2021 ; Randazzo et al 2020 ), India (Kumar et al 2022a , 2021 , 2020 ), Brazil (Ayrimoraes et al n.d. ; Chernicharo et al 2021a ; Claro et al 2021 ; Fongaro et al 2021a , 2021b ; Pepe Razzolini et al 2021 ; Prado et al 2020 ; Salvato et al 2021 ), and Australia (Ahmed et al 2021 , 2020 ), and in surface water or underground water: Iran (Jeddi et al 2022 ), Mexico (Mahlknecht et al 2021 ; Rosiles-González et al 2021 ; Zarza et al 2022 ), India (Kumar et al 2022a , 2022b , 2021 , 2020 ), Ecuador (Guerrero-Latorre et al 2020a ), Brazil (Fongaro et al 2021a ; Pepe Razzolini et al 2021 ), Serbia (Kolarević et al 2021 ), and Dominican Republic (Rodríguez Rodríguez et al 2021 ). Many of these studies focused their analyses on sampling sewage at treatment plant influents or at intermediate locations, such as sewage pumping stations, since those points concentrate the wastewater of the monitored population.…”
Section: Introductionmentioning
confidence: 99%